Women's Safety and Gender-Based Violence in the Republic of North Macedonia - Tozija, Fimka (Frontiers in Public Health, 2020)
Violence against women in the Republic of North Macedonia is the most common form of human rights violation, and women's safety is thus a high-priority public health problem. There have been significant achievements in the area of policy development: legislation harmonization for human rights protection, prevention of violence against women, protocols for the treatment and support of female victims, especially those with disabilities, and further collaboration and coordination between different sectors. In practice, there is still a need to establish a system of institutions for effective prevention, protection, gathering of evidence, and support of women victims of gender-based violence in addition to the prosecution of perpetrators. Policies for the improvement of women's safety should be considered as a priority and undertaken at an individual, relationship, community, and society level.